2010
DOI: 10.1258/td.2010.090508
|View full text |Cite
|
Sign up to set email alerts
|

Scrub typhus in Southern India: are we doing enough?

Abstract: Scrub typhus is a potentially fatal infectious disease caused by Orientia tsutsugamushi. We report on a retrospective analysis of clinical manifestations, lab investigations and outcome of patients admitted to our hospital from January 2009 to December 2009 with scrub typhus. The Weil-Felix test was the serological method used to diagnose scrub typhus. A total of 29 patients were diagnosed with scrub typhus and the majority of them presented with fever (100%), headache (51%), myalgia (51%) and gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Outbreaks are reported during the cooler months of the year in parts of South India like Tamil Nadu and Pondicherry, particularly during the post monsoon period of November through March. Cooler climate in areas, which provide optimum condition for the mites to survive, forecasts the outbreak of scrub typhus [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks are reported during the cooler months of the year in parts of South India like Tamil Nadu and Pondicherry, particularly during the post monsoon period of November through March. Cooler climate in areas, which provide optimum condition for the mites to survive, forecasts the outbreak of scrub typhus [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…People with scrub typhus develop a high fever, maculopapular rash, skin eschars, lymphadenopathy, headache, and myalgia (3). The diagnosis of scrub typhus is based on the patient's exposure history, the clinical features, and the results of serologic testing (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of scrub typhus is based on the patient's exposure history, the clinical features, and the results of serologic testing (4,5). It occurs in persons who engage in occupational or recreational behavior that brings them into contact with mite-infested habitats such as brush and grass (3,(6)(7)(8)(9)(10). In such environments, trombiculid mite larvae can be found in any location that is suitable for rodent populations and has ground moisture sufficient to nourish the mite vectors (11).…”
Section: Introductionmentioning
confidence: 99%
“…6 In last few years there have been outbreaks of scrub typhus in states of south India especially Karnataka. 5 Scrub typhus is transmitted to humans by the bite of larval trombiculid mites. These larval mites usually feed on the wild rats.…”
Section: Discussionmentioning
confidence: 99%
“…8 The occurrence of eschar is less frequent among South-East Asian patients. 5 It has been reported that in dark-skinned patients early eschar could be easily overlooked and the eschar may be very small. 9 It is important to carefully examine the front chest, areas where the skin is folded and areas within 30 cm below the umbilicus in both sexes, lower limbs of males and the front chest and back in females for Eschars.…”
Section: Discussionmentioning
confidence: 99%